Pencegahan Kekerasan Seksual dalam Perspektif Hak Asasi Manusia - Siti Rahayu; Eti Yusnita; Erik Darmawan (Prodi Ilmu Politik FISIP Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research is entitled Analysis of Permendikbud No. 30 Year 2021 on Prevention and Handling of Sexual Violence in Higher Education in the Perspective of Human Rights. Sexual violence is an abuse of human rights (AHR). Sexual violence can occur in the public or private domain. In Indonesia, sexual violence can also occur in the educational environment. Based on the level of education, higher education ranks first in the occurrence of sexual violence. Permendikbud No. 30 Year 2021 as a regulation aimed Prevention and Handling of Sexual Violence in Higher Education. The research problem is related to the formulation process and human rights protected by the Permendikbud No. 30 Year 2021. This study aims to determine the formulation process and human rights protected by the regulation in terms of Human Rights Theory. With this type of qualitative research using a descriptive analysis approach with data sources obtained through draft regulations, books, journals, media, online news, and others. The results of this study is Permendikbud No. 30 of 2021 was born due to a political process through demands from elements of the community to the Indonesian Ministry of Education and Culture. The demand urges the Ministry of Education and Culture of the Republic of Indonesia to immediately make regulations regarding sexual violence and enforce justice for victims of sexual violence in universities. From these demands gave a positive response from the Ministry of Education and Culture of the Republic of Indonesia in the future with the issuance of Regulation of the Permendikbud No. 30 of 2021 on Prevention and Handling of Sexual Violence in Higher Education. Besides that, Permendikbud No. 30 Year 2021 to fulfill and protect Human Rights. There are 26 human rights protected by Permendikbud No. 30 Year 2021. Keywords: Sexual Violence, Human Rights, Permendikbud No. 30 Year 2021